Subjectivity and Personal Ambition in the Governance of Educational Institutions - Indah Siti Nurhalizah; Pitriani Pitriani; Maila Rosidah; Muhammad Sirozi (Journal of Social Work and Science Education, 2026)
This study examines how subjectivity and personal ambition influence the governance of educational institutions and affect the quality and relevance of educational services. Conducted using a qualitative literature review approach, the study analyzed books, journal articles, and policy documents related to educational management, leadership, and organizational governance through content analysis. The findings indicate that when decisions are influenced by personal interests, they can lead to bias, internal conflict, and reduced educational quality. Effective governance requires systematic, transparent, and participatory planning supported by ethical and professional leadership. In Islamic educational contexts, embedding moral and spiritual values such as justice, integrity, and responsibility further strengthens governance and leadership effectiveness. The novelty of this study lies in emphasizing the combined impact of human factors and ethical frameworks on educational management, highlighting the need for moral considerations alongside administrative systems. Practically, the findings suggest that educational institutions should implement objective decision-making processes and foster ethical leadership to enhance accountability and sustainability. Overall, this study contributes a comprehensive framework for understanding how subjectivity and personal ambition affect governance and provides guidance for improving institutional quality and long-term relevance in education.